n = 1 ∑ ∞ ( x 1 ) n cos 6 0 n = n = 1 ∑ ∞ ( x + 1 1 ) n cos 6 0 n
The equation above is satisfied when x = c a + b , where a , b and c are coprime positive integers and x > 0 .
What is the value of a + b + c ?
Note: This problem is in degrees.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
How did you derive your expression for P + i Q on line 4?
Does this help now?
I believe that there is a mistake where you "rationalise the denominator". You have
x − cos θ − i sin θ x
Which when you rationalise the denominator turns into
x 2 + 1 − 2 x cos θ x 2 − x cos θ + i x sin θ
There is a missing factor of x in one of the terms in the numerator in your work.
Sorry. That is a mistake in copying down my workings
In the problem, there should be parentheses around the fractions. For example, "\left( \frac{1}{x} \right)^n" will produce ( x 1 ) n .
Using the fact c o s α = R e ( e i α ) (where i = √ ( − 1 ) ) and summing the series on each side (they are infinite G.P. series each) we get x 2 − 3 x − 1 = 0 . Solving this we get the positive value of x equal to 2 3 + √ 1 3 . So a = 3 , b = 1 3 , c = 2 . Hence a + b + c = 3 + 1 3 + 2 = 1 8
Problem Loading...
Note Loading...
Set Loading...
Let P = 1 + x 1 cos θ + x 2 1 cos 2 θ + x 3 1 cos 3 θ . . .
Let Q = x 1 sin θ + x 2 1 sin 2 θ + x 3 1 sin 3 θ
(Note that these two series converge)
P + i Q = 1 + x 1 ( cos θ + i sin θ ) + x 2 1 ( cos 2 θ + i sin 2 θ ) + x 3 1 ( cos 3 θ + i sin 3 θ ) . . .
Where i = − 1
P + i Q = 1 + x 1 e i θ + x 2 1 e i 2 θ + x 3 1 e i 3 θ
This is a geometric sequence with a common ratio of x 1 e i θ .
So the converging series is equal to 1 − x 1 e i θ 1 = x − e i θ x = ( x − cos θ ) − i sin θ x
Rationalising the denominator we get x 2 + 1 − 2 x cos θ x 2 − x cos θ + i x sin θ
Taking the real part of the equation, P = x 2 + 1 − 2 x cos θ x 2 − x cos θ .
Substituting θ = 6 0 : P = 2 x 2 − 2 x + 2 2 x 2 − x .
So 2 x 2 − 2 x + 2 2 x 2 − x − 1 = 2 ( x + 1 ) 2 − 2 ( x + 1 ) + 2 2 ( x + 1 ) 2 − ( x + 1 ) − 1
Solving for x we find that x 2 − 3 x − 1 = 0
x = 2 3 + 1 3
Therefore a + b + c = 1 8